2015
DOI: 10.1007/s10068-015-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monascus as a nitrite substitute on color, lipid oxidation, and proteolysis of fermented meat mince

Abstract: Monascus spp. are fungi, traditionally eaten in Asian countries, that have the the potential to be used as a nitrite substitute in meat-product processing. Effects of using Monascus ruber MJ-1 as a nitrite substitute on color, lipid oxidation and proteolysis of fermented meat mince were investigated in this study. After 4 days of fermentation, a* and L* values for the samples were significantly higher and lower than the values for the control, respectively; however, b* values were significantly lower than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…M. ruber contains monacolin and azaphilone pigment. Recent studies have investigated M. ruber as an alternative to nitrite substitutes in meat processing [11].…”
Section: Introductionmentioning
confidence: 99%
“…M. ruber contains monacolin and azaphilone pigment. Recent studies have investigated M. ruber as an alternative to nitrite substitutes in meat processing [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among them Mihalcea et al (2018) showed a promising example of total sodium nitrite replacement, without compromising the sensory characteristics and microbial safety of parizer (a frankfurter-like product) by the addition of a sea buckthorn groat. The results obtained by Yu et al (2015) suggested that Monascus strains can be use as a sodium nitrite substitute in the meat processing. HHP (High Hidrostatic Pressure), a novel non-thermal technology, has an immense potential for ensuring the microbiological safety, simultaneously maintaining the sensory quality of meat products (Alahakoon et al, 2015).…”
Section: Future Trendsmentioning
confidence: 99%
“…Additional studies on the antimicrobial effects of Monascus fermentation reported that gram-positive bacteria are more susceptible to inhibition than gram-negative bacteria, and Latobacillus ‘ resistance is negligible [ 74 , 75 , 76 ]. This result encouraged the use of a Monascus pigment as a replacement for nitrite in meat production [ 77 ]. The specific mechanisms and properties of this finding are still unknown; however, the finding suggests that antimicrobial activity is significantly determined by cell growth conditions and culture medium compositions [ 72 , 73 , 78 ].…”
Section: Antimicrobial and Antiviral Effects Of Monascusmentioning
confidence: 99%